2015
DOI: 10.1134/s1990341315020030
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the RCR catalog sources in the millimeter and submillimeter ranges based on the Planck mission data

Abstract: We have studied the regions of the microwave background radiation maps of the Planck experiment in the neighborhood of the RCR catalog radio sources. From the processed data for bright radio sources in the microwave range, we plotted the calibration curves which allow the brightness of the objects to be measured. For the first time, for 117 objects we obtained estimates of flux density at the millimeter and submillimeter waves, prepared the spectra, conducted identification, and gathered available information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…For the faint objects, which have no Planck measurements we estimated the upper flux density limit using the technique proposed in [60]. We used the maps of the microwave emission components obtained by Planck space telescope 4 [59], and the Planck source catalogs, which are available from the Planck Legacy Archive -PLA 5 .…”
Section: The Flux Densities Estimation At Millimeter and Submillimete...mentioning
confidence: 99%
See 2 more Smart Citations
“…For the faint objects, which have no Planck measurements we estimated the upper flux density limit using the technique proposed in [60]. We used the maps of the microwave emission components obtained by Planck space telescope 4 [59], and the Planck source catalogs, which are available from the Planck Legacy Archive -PLA 5 .…”
Section: The Flux Densities Estimation At Millimeter and Submillimete...mentioning
confidence: 99%
“…There is a hypothesis about the increased likelihood of a positive response ("hot spots") on microwave background maps if a radio galaxy is located there [61]. It was shown that a fairly large number of extragalactic point sources with different spectral properties are detected at the 4σ on Planck maps containing signals of both the frequency channels and the cleaned CMB [60,62]. We used Aladin application [63,64] to identify the spots with the objects studied and to measure the distance from the source to the center of the spot.…”
Section: The Flux Densities Estimation At Millimeter and Submillimete...mentioning
confidence: 99%
See 1 more Smart Citation
“…One way to solve it is to use masking from known sources (Ade et al, 2014h). However, as was shown in the works Verkhodanov et al (2015aVerkhodanov et al ( , b, 2016a, in which the fluctuations of the microwave background on the Planck frequency maps and CMB maps in the direction of the radio sources of the RCR catalog (RATAN Cold Refined) (Soboleva et al, 2010), at a level below the sensitivity threshold (less than ), a sufficiently large number of positive peaks are registered, which can be manifestations of either point extragalactic sources or background galactic components. Inhomogeneities of the positive signal on the Planck frequency maps in the millimeter and submillimeter ranges were also detected near GPSs (Gigahertz-Peaked spectrum)-objects observed on the RATAN-600 radio telescope in the period 2006-2017.…”
Section: 5 ′ ±mentioning
confidence: 68%
“…Earlier we already used the approach based on selecting cluster candidates using the SZeffect in the direction of radio sources (see [25][26][27]). In this study we continue developing the field related to an automated SZ-object selection algorithm based on machine learning methods (see the description of the first experiment in [28]).…”
mentioning
confidence: 99%